How do learners respond to computer based learning material which has been designed to suit their particular learning style - Hassan, Razali (2008)
The development of ICT in education has changed the nature of people's learning. The evolution of Computer Based Learning (CBL) to virtual learning has had a huge effect on learning methodology. Learning theories from behaviourism, cognitivism and constructivism have been re-assessed. This study explored students' feedback and experiences when using CBL material which has been adapted to particular learning styles. Studies show that individuals learn in different ways. They have different preferences in collecting, organizing and delivering information. These differences impact on learning outcomes. The framework in this study concerns itself with modal preferences known as the VARK Model. The study focuses on CBL material which has been designed for learning new software. This learning material was designed with four different learning routes to appeal to those with dominant Visual, Aural, Reading and Kinaesthetic preferences respectively. The learning package was called the MINDs learning system. Respondents involved were student teachers in two Universities in the UK and Malaysia. Sixty two respondents agreed to participate interviews and in trialling courseware. Data was collected through questionnaire, survey, interview and observation. Quantitative and qualitative data was analysed descriptively, triangulation of the findings was carried out and conclusions were drawn. Findings from the study show that learning styles instruments measure general preferences rather than offering an indication of the specific context in which learning takes place. Matching learning material with particular learning styles did not significantly increase motivation, comprehension or have a major impact on learning. However, learners are aware of having learning styles and found that learning with suited learning preferences made them feel more comfortable. Recommendations were put forward for future research to design and develop a 'new type' of CBL material which takes into account individual learning preferences.